Music Performance and Music Theory Disciplines: their Interconnection, Significance, and Effective Aspects (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article examines the importance of music theory in improving the professional skills of music performers, and highlights a number of shortcomings of music performers currently studying in specialized music educational institutions.